Pengaruh Media Sosial Dalam Meningkatkan Niat Beli Karang Hias (Coral) Pada PT. Dirga Mega Cipta Bekasi, Jawa Barat - Magfirah Magfirah; Akmal Abdullah; Ilham Ilham (Master Manajemen, 2024)
This study aims to determine which of Facebook and Instagram has the most dominant effect on increasing the purchase intention of Ornamental Coral at PT Dirga Mega Cipta Bekasi. The type of research used in this research is quantitative research. The population in this study were all Facebook and Instagram social media followers on the @coral education and @coral_educational accounts. The sample in this study amounted to 39 people using random sampling analysis techniques, The data collection technique used a questionnaire with a Likert scale, each of which had been tested and had met the validity and reliability requirements. The data processing technique used SPSS version 22. The data analysis technique used in this study is multiple linear regression. The results of this study can show that Facebook and Instagram social media have the most dominant influence in increasing purchase intention on Ornamental Corals is Facebook Social Media.